P091 Who do we risk leaving behind? A survey of digital access and e-health literacy in people with inflammatory conditions. (23rd April 2022) - Hider, Samantha; Muller, Sara; Gray, Lauren; Manning, Fay; Brooks, Mike; Heining, Dominic; Menon, Ajit; Packham, Jonathan; Raghuvanshi, Subhra; Roddy, Edward; Ryan, Sarah; Scott, Ian; et al.
Abstract: Background/Aims: The COVID-19 pandemic led to an overnight shift in healthcare delivery and rapid uptake of digital technology. Such approaches risk digital exclusion for people without access to or not confident in their use of technology. We sought to examine digital access and e-health literacy in people with inflammatory conditions. Methods: People (n = 2, 024) were identified from their electronic health record and invited to participate in a survey, using SMS and postal approaches. Data were collected on age, gender, self-reported arthritis diagnosis (RA, PsA, AS, SLE and other), access to an internet-enabled device and frequency of internet access, health literacy (single-item literacy screener) and self-perceived e-health literacy (eHEALs). Ethical approval was obtained (Ref 21/PR/0867). Results: 639 people completed the survey, of whom 287 (44.9%) completed it online. Mean (sd) age was 64.5 (13.1) years and 384 (64.7%) were female. 98.3% were white. Approximately 20% of people did not have access to an internet enabled device (Table). 93 (15.3%) of patients reported never accessing the internet, this proportion was higher in people with RA. Approximately 19% had low health literacy. In those reporting internet use, eHealth literacy was moderate. The most popular options for accessing arthritis advice were telephone helplines or appointments. Conclusion: Low health literacy, lack of digital access and low reported internet use was common, especially in people with RA, leading to high use of telephone advice and rheumatology appointments. Digital roll-out needs to take account of people requiring extra support to enable them to access care or risks excluding many patients with inflammatory conditions. Disclosure: S. Hider: None. S. Muller: None. L. Gray: None. F. Manning: None. M. Brooks: None. D. Heining: None. A. Menon: None. J. Packham: None. S. Raghuvanshi: None. E. Roddy: None. S. Ryan: None. I. Scott: None. Z. Paskins: None.